“Intrinsic” elimination rate and dietary intake estimates for selected indicator PCBs: Toxicokinetic modeling using serial sampling data in US subjects, 2005–2010 - Aylward, L.L.; Collins, J.J.; Bodner, K.M.; Wilken, M.; Bodnar, C.M. (Chemosphere (Oxford), 2014)
•Polychlorinated biphenyls (PCBs) measured in blood from 43 subjects 5years apart.•Apparent half-lives (HLs) calculated based on changes in levels and body burdens.•Intrinsic HLs from previous studies used to estimate dietary intakes over 5years.•Data support intrinsic half-lives of approximately 5years for PCBs 105 and 118.•Intrinsic HLs of 10, 15, and >20years for PCBs 138, 153, and 180 are indicated. Changes in measured concentrations of persistent compounds such as polychlorinated biphenyls (PCBs) in an individual over time reflect not only intrinsic elimination rates but also any ongoing intake of the compounds and changes in the volume of distribution. Thus, “apparent” elimination rates calculated from data on changes in serum lipid-adjusted concentration may over- or under-estimate the “intrinsic” elimination rates for such compounds. Serum PCB concentrations were measured in 43 individuals approximately 5years apart. Changes in measured concentrations and body weights were used to estimate mass-based apparent elimination rates. The changes in estimated body mass of PCBs 105, 118, 138, 153, and 180 were input into a simple first-order model employing previously estimated intrinsic elimination rates to estimate congener-specific average dietary intake rates over the period between samples. Calculated median dietary intakes were compared to previous estimates. Intrinsic elimination rates were adjusted for two congeners. The analyses support central tendencies of intrinsic elimination rates of approximately 5years for PCBs 105 and 118, 11years for PCB 138, 14.4years for PCB 153, and 20years or more for PCB 180. Estimated dietary intakes for this population and time period depend on the assumed intrinsic elimination rates and range from 0.1ngkg−1d−1 for PCB 105 to approximately 1–2ngkg−1d−1 for PCB 180. Estimated body burdens of PCB 180 changed very little over the five-year period, suggesting near steady-state exposure levels. As a result, estimates for both elimination half-life and ongoing intake rates for this congener are highly uncertain.